Pengaruh Ilmu Sosial terhadap Mutu Pendidikan Siswa - Amini Amini; Fauziah Nurkhairiwa; Indra Maulana; Ilham Satriawan; Ivo Fatmala Sinaga; Wahyuni Pandiangan (Journal on Education, 2023)
This study aims to describe the impact of learning social sciences on educational change where this change is an increase in quality which will later be useful for future students. Education has a very important role in the development of the Indonesian human being as a whole. Therefore education really needs to be developed from various sciences, because quality education can increase the intelligence of a nation. Education is an important part of the national development process which contributes to increasing a country's economic growth. Education is also an investment in the development of human resources where increasing skills and abilities is believed to be a supporting factor for human efforts in navigating life. The purpose of education based on the principles of Pancasila has the aim of increasing piety to God Almighty, intelligence, skills, enhancing character, strengthening personality so that they can develop themselves and are jointly responsible for the development of the nation. The quality of education needs to be considered to achieve educational goals, while the quality itself can be seen from the success achieved by a student while participating in teaching and learning activities.